Global prevalence of fatigue in patients with multiple sclerosis: a systematic review and meta-analysis - Yi, Xiaodong; Zhang, Yue; Du, Qiufeng; Kang, Jing; Song, Shuang; Li, Tao; Jiang, Yunlan (Frontiers in Neurology, 2024)
Background Fatigue is one of the most common and burdensome symptoms for patients with multiple sclerosis (PwMS), considerably impacting their quality of life and employment. Numerous reports have described the prevalence of MS-related fatigue, but there is no global consensus on this matter. Objective To examine the global prevalence of MS-related fatigue and identify sources of heterogeneity in the published literature. Methods A systematic review and meta-analysis were conducted. A comprehensive search of the PubMed, EMBASE, Cochrane Library, Web of Science, PsycINFO, CINAHL, China National Knowledge Infrastructure (CNKI), and Wanfang database for potential literature from 2000 to January 31, 2024. A random effects model was used to calculate the prevalence of MS-related fatigue. Subgroup analyses and a meta-regression were used to explore the sources of heterogeneity. Results Sixty-nine studies from 27 countries were included. The global prevalence of MS-related fatigue was 59.1%, and it has decreased every decade since 2000. Fatigue was prevalent among females, those with lower education levels, those who were older, those with greater disability, and those with longer MS durations. The meta-regression revealed that fatigue measurement instruments were the largest source of heterogeneity. Conclusion The prevalence of MS-related fatigue is quite high. Healthcare professionals should screen for and manage fatigue for PwMS as early as possible and pay attention to populations with a high prevalence of fatigue. The high heterogeneity among the prevalence rates due to differences in the fatigue scales suggests the importance of reaching a consensus on the best screening tools for MS-related fatigue.